Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/tbed.12112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Porcine Circovirus Type 2 Infections on Bovine Tuberculosis in Wild Boar Populations

Abstract: SummaryThe wild boar is an important reservoir of bovine tuberculosis (bTB) in southwestern Spain. Some risk factors such as wild boar density or age have been associated with the presence of high prevalences of bTB in wild boar. However, the influence of other risk factors such as co-infections with other pathogens has not yet been studied. This work aims to assess the influence of porcine circovirus type 2 (PCV-2) infection on bTB prevalence and bTB lesional patterns observed in wild boar. The presence of bT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Such scenario may facilitate interaction with other pathogens, a fact that should be taken into account when dealing with the epidemiology of natural infections. Globally, this situation may have implications regarding the assessment and even the efficacy of future disease control measures [46, 58]. This confirms the view that in natural settings multipathogen approaches are more realistic than single-pathogen ones.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Such scenario may facilitate interaction with other pathogens, a fact that should be taken into account when dealing with the epidemiology of natural infections. Globally, this situation may have implications regarding the assessment and even the efficacy of future disease control measures [46, 58]. This confirms the view that in natural settings multipathogen approaches are more realistic than single-pathogen ones.…”
Section: Discussionmentioning
confidence: 78%
“…For comparison, Vicente et al [36] recorded 38% antibody prevalence against PCV2 in fenced wild boar piglets, and Boadella et al [29] found 47%. Regarding coinfection data on these pathogens and Risco et al [46] found correlations between PCV2 infection prevalence and TB prevalence in wild boar in other high TB and PCV2 prevalence sites in Mediterranean Spain. By contrast, both PCV2 and TB have a much lower prevalence (<10%) in Spanish regions with a more humid Atlantic climate where, interestingly, generalized TB appears to be less common [37, 47].…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, certain pathogen combinations are correlated to more severe bTB lesions in wild boar. Since the presence of animals displaying severe bTB lesion patterns has been recently related to higher bTB prevalence in wild boar populations [19] , programs aimed at bTB management and control in wild boar populations should take into account the effects of concomitant pathogens on the disease severity. The relationship between PCV2, Metastrongylus spp and ADV on bTB severity suggests that sanitary measures focused on the control of these agents (i.e., deworming or vaccination against viruses), may help to reduce the bTB prevalence in the affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the African buffalo, nematode infection not only is likely to increase bTB susceptibility [17] , but also to accelerate mortality due to body condition impairment in co-infected individuals [18] . A positive relationship between porcine circovirus type 2 (PCV2) and bTB prevalences has also recently been observed in wild boar populations from mid-western Spain [19] ; however little is known about the role of other common pathogens in wild boar in bTB dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In Mediterranean Spain, correlations were found (at the population level) between wild boar TB prevalence, generalized TB and the prevalence of porcine circovirus type 2, a widespread immunosuppressive virus (Risco et al. ). However, such correlations were less evident at the individual animal scale (Díez‐Delgado et al.…”
Section: Host Pathology Ecology and Tb Epidemiologymentioning
confidence: 99%